2005
DOI: 10.2169/internalmedicine.44.311
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Polycystic Kidney Disease Showing Rupture of a Lateral Ventral Hernia Following Paralytic Ileus

Abstract: We report an 83-year-old Japanese male with autosomal dominant polycystic kidney disease (ADPKD), which was marked by unusually enlarged kidneys, and in whom ileus occurred after administration of procainamide. The bowels became swollen and ruptured the skin and appeared on the outside of the skin. Even after the ileus state was resolved, the projected intestinal tract was not restored due to a large defect of the skin, and ostomy was performed. Abdominal hernia including lateral ventral hernia due to enlarged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The uremia, infection, fluid and electrolyte imbalance, cystic fluid, retroperitoneal blood and irrigation fluid extravasation all would have caused the paralytic ileus. In 2 patients the multiple cysts and retroperitoneal fluid were aspirated which led to recovery from ileus, similarly reported by others [20,21]. …”
Section: Discussionsupporting
confidence: 61%
“…The uremia, infection, fluid and electrolyte imbalance, cystic fluid, retroperitoneal blood and irrigation fluid extravasation all would have caused the paralytic ileus. In 2 patients the multiple cysts and retroperitoneal fluid were aspirated which led to recovery from ileus, similarly reported by others [20,21]. …”
Section: Discussionsupporting
confidence: 61%
“…In patients with ADPKD, intestinal compression due to enlarged liver and kidneys has been reported to cause gastrointestinal symptoms, including upper digestive tract symptoms, such as heartburn, nausea, vomiting, loss of appetite, and early satiety; severe constipation; and odd-shaped feces [ 1 ]. Kato et al reported a case of a giant cystic kidney in which perforated intestine protruded out of the abdominal wall because of thinning of the abdominal wall after the onset of paralytic ileus of the small intestine [ 3 ]. Several papers reported that intestinal perforation was common in patients with cystic kidneys and hypothesized that the diverticulum was the cause; however, none of the reported studies could prove that the diverticulum was involved at the site of the perforation.…”
Section: Discussionmentioning
confidence: 99%
“…The latter include gastrointestinal complications; for example, colonic diverticulosis has been reported to be common [ 2 ]. Another gastrointestinal complication is ileus, which is caused by compression of the gastrointestinal tract due to enlargement of the liver and kidneys [ 3 ]. Here, we report a case of ADPKD with a markedly enlarged kidney, whose intestinal perforation led to an enterocutaneous fistula of the abdominal wall, allowing intestinal fluid to spread systemically.…”
Section: Introductionmentioning
confidence: 99%